(untitled) - Mintzberg, Henry (Englewood Cliffs, N. J., 1979)
Book is a synthesis of the empirical literature currently available on organizational structuring. A framework is developed enabling students to handle organizational problems. For use as a supplement in upper level Organizational Design courses in Management.
Keywords: Industrial organization,Tổ chức công nghiệp